PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA KELAS II SD NEGERI 064971 MEDAN TEMBUNG TAHUN PEMBELAJARAN 2024/2025 - Jenni Parlopes Tarigan; Indah Pratiwi; Roida Siboro (STKIP Subang, 2024)
This study started from the low learning outcomes of second-grade students at SDN 064971 Medan Tembung. To overcome this, the author applied a problem-based learning model (PBL) with the aim of improving student learning outcomes. This study is a classroom action research involving second-grade students of SDN 064971 Medan Tembung as subjects. The results of the study showed an increase in student learning outcomes in mathematics, especially number material, after improvements were made to the actions in cycle II. In the early stages, only 4 students (18%) achieved completion with an average score of 46.81. After cycle I, the number of students who completed increased to 10 people (45%) with an average score of 63.18. In cycle II, 18 students (82%) achieved completion with an average score of 76.81. The action was stopped in cycle II because the success criteria had been achieved. From this study, it can be concluded that the application of the problem-based learning model succeeded in improving the mathematics learning outcomes of second-grade students at SDN 064971 Medan Tembung.